Psycho-Social factors as correlates of anti-social behaviour among secondary school adolescents in Oke-Ogun area, Oyo state (2011)
The study investigated some psycho-social factors as correlates of anti-social behaviors among secondary school adolescents in Oke-Ogun Area, Oyo State. Descriptive survey research design was employed. A multi-stage random sampling technique was employed in selecting 694 participating adolescents from two Local Government randomly selected from the list 9 Local Government in Oke-Ogun Area of Oyo State. Their age ranged between 11 years and 19 years with the mean age of 12.6 years and the standard deviation 4.57. Pearson’s Product Moment Correlation and Multiple regression analysis was used to analyse the data. The results demonstrated that each of the psycho-social factors jointly influence anti-social behaviors among secondary school adolescents, but peer relation is the most potent factor that influences anti-social behaviors. The implications of the findings for educational and counselling practice were highlighted.